Voltammetric Determination of the Iodide/Iodine Formal Potential and Triiodide Stability Constant in Conventional and Ionic Liquid Media - Bentley, Cameron L; Bond, Alan M; Hollenkamp, Anthony F; Mahon, Peter J; Zhang, Jie (Journal of physical chemistry. C, 2015)
The iodide/triiodide/iodine (I–/I3 –/I2) redox system has been the subject of electrochemical investigations for well over half a century and remains a contemporary research interest due to the integral role of the I–/I3 – couple in dye-sensitized solar cell (DSSC) technology. In this study, we have calculated the formal potential (E 0′) of the I–/I2 process and the stability constant (K stab) of I3 – in two protic solvents (water and ethanol), two aprotic solvents (acetonitrile and propylene carbonate), eight aprotic ionic liquids (AILs), and one protic ionic liquid (PIL) using the voltammetric methodology developed herein. Furthermore, using 1-ethyl-3-methylimidazlium bis(trifluoromethanesulfonyl)imide (abbr. [C2mim][NTf2]) as a “model” ionic liquid-based DSSC electrolyte system, we have also investigated the influence of three common additives/impurities in DSSCs (i.e., tert-butylpyridine, Li+, and water) on the parameters E 0′(I–/I2) and K stab and characterized two analogous redox systems, Br–/Br3 –/Br2 and SeCN–/(SeCN)3 –/(SeCN)2. E 0′(I–/I2) and K stab(I3 –) increase in the order ethanol ≈ acetonitrile < propylene carbonate < AILs < PIL < water; and water < ethanol ≈ PIL < acetonitrile ≈ AILs < propylene carbonate, respectively. In the presence of the additives/impurities (see above), E 0′(I–/I2) and K stab increase in the order 0.5 M tert-butylpyridine < neat [C2mim][NTf2] ≈ 0.3 M Li+ < 2 wt % water and 0.5 M tert-butylpyridine ≪ 2 wt % water < 0.3 M Li+ ≈ neat [C2mim][NTf2], respectively. Finally, E 0′(X–/X2) and K stab(X3 –) increase in the order SeCN–/(SeCN)2 ≈ I–/I2 < Br–/Br2 and (SeCN)3 – ≪ Br3 – < I3 –, respectively, in [C2mim][NTf2]. The trends in the (pseudo)halide/(pseudo)halogen formal potentials and tri(pseudo)halide stability constants have been rationalized in terms of the physicochemical parameters (i.e., polarity, Gutmann donor/acceptor numbers, ionic strength, etc.) of the respective solvent/ionic liquid media.